Ancient finite entropy flows by powers of curvature in R2. (March 2022) - Choi, Kyeongsu; Sun, Liming
Abstract: We show the existence of non-homothetic ancient flows by powers of curvature embedded in R 2 whose entropy is finite. We determine the Morse indices and kernels of the linearized operator of shrinkers to the flows, and construct ancient flows by using unstable eigenfunctions of the linearized operator.